A Literature Review: Tax Planning and Avoidance in Earnings Management - Intan Kumala Ratu; Agrianti Komalasari; Liza Alvia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to give a comprehensive analysis of the intricate relationship between tax planning, tax avoidance, and earnings management in the context of corporate financial practices. Through an extensive literature review, the research elucidates the multifaceted implications of these practices on financial reporting, corporate governance, and adherence to international tax regulations. The findings reveal that legal tax planning, when aligned with strategies to reduce taxable income, can positively impact reported earnings. However, the transformation of tax planning into a tool for earnings management raises ethical and transparency concerns, leading to global regulatory scrutiny. The study also investigates the nuanced impact of a declining tax rate on companies' strategies for managing earnings, emphasizing the need for careful consideration and ethical financial practices. Future research directions are proposed, highlighting the importance of empirical investigations across diverse industries and regions to deepen our understanding of the intricate relationship between tax practices and earnings management. The findings contribute valuable insights for stakeholders, practitioners, and policymakers